1999
DOI: 10.1152/ajpheart.1999.277.4.h1513
|View full text |Cite
|
Sign up to set email alerts
|

Acute hyperglycemia depresses arteriolar NO formation in skeletal muscle

Abstract: In the rat intestinal and cerebral microvasculatures, acute D-glucose hyperglycemia suppresses endothelium-dependent dilation to ACh without affecting endothelium-independent dilation to nitroprusside. This study determined whether acute hyperglycemia suppressed arteriolar wall nitric oxide concentration ([NO]) at rest or during ACh stimulation and inhibited nitroprusside-, ACh- or contraction-induced dilation of rat spinotrapezius arterioles. Vascular responses were measured before and after 1 h of topical 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
46
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 27 publications
10
46
1
Order By: Relevance
“…One of the major risks of obesity is that severe insulin resistance can allow occasional or sustained hyperglycemia, which are the hallmarks of type II or insulin-independent diabetes mellitus. In vivo studies in normal rats indicate that acute, Ն300 mg/dl D-glucose hyperglycemia was detrimental to the NO function of normal endothelial cells in intestinal, cerebral, and skeletal muscle vasculatures (5,16,20,22). In the present study, we found the same result in lean Zucker rats (see Figs.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…One of the major risks of obesity is that severe insulin resistance can allow occasional or sustained hyperglycemia, which are the hallmarks of type II or insulin-independent diabetes mellitus. In vivo studies in normal rats indicate that acute, Ն300 mg/dl D-glucose hyperglycemia was detrimental to the NO function of normal endothelial cells in intestinal, cerebral, and skeletal muscle vasculatures (5,16,20,22). In the present study, we found the same result in lean Zucker rats (see Figs.…”
Section: Discussionsupporting
confidence: 84%
“…In lean rats, 200 mg/dl D-glucose was benign, but 300 mg/dl D-glucose for ϳ30-60 min impaired endothelium-dependent NO vasodilation in normal cerebral, intestinal, and skeletal muscle vasculatures (5,16,20,22). We found that less NO was formed after these bouts of acute hyperglycemia as determined by both bioassay and direct measurement of arteriolar wall NO concentration ([NO]) (5,8,16,20). In addition, in vivo flow shear-dependent endothelial regulation, which is NO dependent in the rat intestinal arterioles, was suppressed during acute hyperglycemia (16).…”
mentioning
confidence: 99%
“…There is evidence for both an increase (10, 16, 31, 36) and a decrease (27,36) in the activity of the NO system in the diabetic state. Evidence for increased NO production under hyperglycemic conditions is shown, for example, by the increase in NO release in endothelial cells exposed to high glucose levels (9,16,18).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that hyperglycemia/diabetes mellitus (DM) causes a loss of endothelium-derived NO in both animals (17)(18)(19) and humans (20), but the underlining mechanism is poorly understood. DM does not influence the overall eNOS protein level or its mRNA level (21).…”
Section: Endothelium-derived Nitric Oxide (No)mentioning
confidence: 99%